Purinergic P2X7 Receptor: A Cation Channel Sensitive to Tumor Microenvironment - Scarpellino, Giorgia; Genova, Tullio; Munaron, Luca (Recent Patents on Anti-Cancer Drug Discovery, 2019)
Background: Purinergic signalling is involved in several physiological and pathophysiological processes. P2X7 Receptor (P2X7R) is a calcium-permeable ion channel that is gaining interest as a potential therapeutic target for the treatment of different diseases including inflammation, pain, psychiatric disorders and cancer. P2X7R is ubiquitously expressed and sensitive to high ATP levels, usually found in tumor microenvironment. P2X7R regulates several cell functions, from migration to cell death, but its selective contribution to tumor progression remains controversial. Objective: Current review was conducted to check involvement of P2X7R use in cancer treatment. Methods: We review the most recent patents focused on the use of P2X7R in the treatment of cancer. Results: P2X7R is an intriguing purinergic receptor that plays different roles in tumor progression. Conclusion: Powerful strategies able to selectively interfere with its expression and function should reveal helpful in the development of new anti-cancer therapies.
Keywords: ion channels